The governance of mining and the human security of local community: a case study of the Indonesian coal mining industry - Indriastuti, Suyani (2019)
This thesis explores the ‘disruption’ of human security of local communities by the Indonesian coal mining industry at the level of the individual and also at the aggregate level of the ‘community’. Human security refers to freedom from want (poverty and unemployment), fear (violence and conflict), and indignity (displacement and human rights abuse). As a result of poor mining practices such as land grabbing, deforestation, unmaintained mining pits and waste local communities encounter social and environmental problems. I argue that the principle of commodification, as outlined in Karl Polanyi’s book The Great Transformation, dictates how the mining industry governs the use of land and labour. I also examine counter-movements, including action by local communities, civil society organisations (CSOs) and the state, that aim to ‘decommodify’ land and labour and protect local communities from the detrimental impacts of mining. This study examines East Kalimantan as the most prolific coal-producing province in Indonesia, with high levels of mining investment and revenue. I examine why East Kalimantan has higher levels of poverty and unemployment than the neighbouring provinces of South Kalimantan and Central Kalimantan, which have medium and low levels of mining investment and revenue (respectively). Building on Polanyi’s double movement and using ‘explaining-outcome process tracing’ methods, this research traces commodification and counter-movement during different eras of Indonesian governance: the New Order (1966-1998), the early Reform Era (1999-2009) and the later Reform Era (2009-2015). Process tracing methods are used to analyse how causal processes explain the nexus of commodification, human insecurity, and counter-commodification. I argue that government commitment to economic liberalisation facilitates the commodification of land and labour, and enables disruptive mining practices. In the short term the mining industry can bring employment and economic benefit to local communities. However, this often also brings an immediate cost for those dependent on the land for a living. In the longer term this process is often incompatible with sustainable mining and non-mining related livelihood and the maintenance of the local environment. The end result has been a double or counter-move against the mining industry. I track the governance of mining in Indonesia from centralistic governance under the New Order Era to decentralist governance in the Reform Era. Changing socio-political economic structures have challenged the capabilities of actors to govern the mining industry. Globalisation, democratisation and the demand for decentralisation have all had an impact on the governance of mining. Specifically, weak state effectiveness and political accountability enabled the mining industry to intensify commodification during the early Reform Era (1999-2009). Subsequently the Indonesian government introduced policies (2009-present) to improve the governance of mining and to enhance the human security of local communities within a framework of sustainable economic development.